2009
DOI: 10.1016/j.pain.2009.03.008
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of topical diclofenac containing dimethyl sulfoxide (DMSO) compared with those of topical placebo, DMSO vehicle and oral diclofenac for knee osteoarthritis

Abstract: While topical non-steroidal anti-inflammatory drugs are considered safe, their long-term efficacy for osteoarthritis has been suspect. We conducted a 12-week, double-blind, double-dummy, randomized controlled trial of topical diclofenac (TDiclo) in a vehicle solution containing dimethyl sulfoxide (DMSO) in 775 subjects with radiologically confirmed, symptomatic primary osteoarthritis of the knee. This 5-arm study compared TDiclo with a placebo solution, the DMSO vehicle, oral diclofenac (ODiclo) and the combin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
177
0
6

Year Published

2010
2010
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 179 publications
(186 citation statements)
references
References 38 publications
3
177
0
6
Order By: Relevance
“…The local drug concentration after oral administration is low and the gastrointestinal toxic and side effect are serious (Matsuno et al 2009;Simon et al 2009), while surgery for treatment of OA has shortcomings including high cost, limited efficacy and poor patient compliance (Moseley et al 2002;Rat et al 2010). Moreover, the absorption of transdermal preparations is poor and local skin irritation is inevitable.…”
Section: Introductionmentioning
confidence: 99%
“…The local drug concentration after oral administration is low and the gastrointestinal toxic and side effect are serious (Matsuno et al 2009;Simon et al 2009), while surgery for treatment of OA has shortcomings including high cost, limited efficacy and poor patient compliance (Moseley et al 2002;Rat et al 2010). Moreover, the absorption of transdermal preparations is poor and local skin irritation is inevitable.…”
Section: Introductionmentioning
confidence: 99%
“…9 Similarly, numerous other studies of topical NSAIDs have reported effective relief of OA pain with low rates of dose-related gastrointestinal, cardiovascular, renal, and other systemic AEs; the frequency of these AEs has typically been higher in studies of oral NSAIDs. [7][8][9]17,18 A limitation of this study is that the sample size was not large enough to allow for an analysis of AEs in patients with DDIs based on age and other demographic variables. However, a pooled analysis of 3 trials in which 721 patients with OA of the knees were treated with DSG found no difference in efficacy and similarly low AE rates in patients aged , 65 years versus those aged $ 65 years.…”
Section: Discussionmentioning
confidence: 99%
“…28 Multiple formulations have been trialled including topical ketoprofen 29 and diclofenac sodium 1.5% topical solution in dimethyl sulfoxide. 27 Safety with diclofenac sodium 1% gel has also been shown in the older population in a 12-month, post hoc analysis of patients with knee osteoarthritis. The overall rates of cardiovascular and gastrointestinal adverse events were similar for people under and over 65 years of age.…”
Section: Nsaidsmentioning
confidence: 99%
“…27,28 Efficacy is greater than placebo and comparable to oral NSAIDs. 28 Multiple formulations have been trialled including topical ketoprofen 29 and diclofenac sodium 1.5% topical solution in dimethyl sulfoxide.…”
Section: Nsaidsmentioning
confidence: 99%